Impact of ferumoxytol magnetic resonance imaging on the rhesus macaque maternal–fetal interface. Issue 2 (12th September 2019) - Nguyen, Sydney M; Wiepz, Gregory J; Schotzko, Michele; Simmons, Heather A; Mejia, Andres; Ludwig, Kai D; Zhu, Ante; Brunner, Kevin; Hernando, Diego; Reeder, Scott B; Wieben, Oliver; Johnson, Kevin; et al.
Abstract: Ferumoxytol is a superparamagnetic iron oxide nanoparticle used off-label as an intravascular magnetic resonance imaging (MRI) contrast agent. Additionally, ferumoxytol-uptake by macrophages facilitates detection of inflammatory sites by MRI through ferumoxytol-induced image contrast changes. Therefore, ferumoxytol-enhanced MRI holds great potential for assessing vascular function and inflammatory response, critical to determine placental health in pregnancy. This study sought to assess the fetoplacental unit and selected maternal tissues, pregnancy outcomes, and fetal well-being after ferumoxytol administration. In initial developmental studies, seven pregnant rhesus macaques were imaged with or without ferumoxytol administration. Pregnancies went to term with vaginal delivery and infants showed normal growth rates compared to control animals born the same year that did not undergo MRI. To determine the impact of ferumoxytol on the maternal–fetal interface (MFI), fetal well-being, and pregnancy outcome, four pregnant rhesus macaques at 100 gestational day underwent MRI before and after ferumoxytol administration. Collection of the fetoplacental unit and selected maternal tissues was performed 2–3 days following ferumoxytol administration. A control group that did not receive ferumoxytol or MRI was used for comparison. Iron levels in fetal and MFI tissues did not differ between groups, and there was no significant difference in tissue histopathology with or without exposure to ferumoxytol, and no effect on placental hormone secretion. Together, these results suggest that the use of ferumoxytol and MRI in pregnant rhesus macaques does not negatively impact the MFI and can be a valuable experimental tool in research with this important animal model. Abstract : Summary Sentence : Ferumoxytol magnetic resonance imaging for non-invasive pregnancy monitoring of the rhesus macaque does not impact histopathology or iron content of the maternal–fetal interface.